Implementasi Dzikir sebagai Terapi Sufistik untuk Mencegah Stres pada Ibu Rumah Tangga - Ismi Rahma Marwiyah (Gunung Djati Conference Series, 2023)
This study aims to determine the implementation of dhikr as a mystical therapy to prevent stress on housewives. The method used in this research is qualitative with literature review, or researching existing books or articles. The results of this research and discussion found that methods of implementing dhikr that can be used for sufistic therapy for housewives include reciting dhikr after prayer, dhikr in tahlil, reading blessings, asmaul husna, murottal Al-Qur'an and dhikr prayer. This study concludes that the application of dhikr is the same as dhikr in general, but focuses more on the therapeutic media aspect as a form of treatment for housewives which can be done independently at home.